2009
DOI: 10.1007/s10964-009-9460-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Orientation as a Moderator of the Relationship Between Chinese American Adolescents’ Discrimination Experiences and Delinquent Behaviors

Abstract: The purpose of this study was to examine the relationships among Chinese American adolescents' discrimination experiences, cultural orientations, and delinquent behaviors. Data were collected from three hundred and eleven Chinese American adolescents (58% girls) and their parents when the adolescents were 7th or 8th graders and again 4 years later. The data analyses demonstrated that adolescents' perceptions of discrimination and victimization experiences were significantly related to their delinquent behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 62 publications
(136 reference statements)
3
35
0
Order By: Relevance
“…In the same study, Deng et al (2010) found the same interaction between discriminatory victimization and cultural orientation in predicting delinquency-the positive relationship between discriminatory victimization and delinquent behavior was only significant for individuals who reported a low Western cultural orientation. In the face of high levels of discriminatory victimization, the association between discrimination and delinquency was not significant for Chinese American adolescents who reported high levels of Western cultural orientation.…”
Section: Acculturationmentioning
confidence: 72%
See 1 more Smart Citation
“…In the same study, Deng et al (2010) found the same interaction between discriminatory victimization and cultural orientation in predicting delinquency-the positive relationship between discriminatory victimization and delinquent behavior was only significant for individuals who reported a low Western cultural orientation. In the face of high levels of discriminatory victimization, the association between discrimination and delinquency was not significant for Chinese American adolescents who reported high levels of Western cultural orientation.…”
Section: Acculturationmentioning
confidence: 72%
“…Considering discrimination events in Western cultural societies, several researchers have demonstrated that the stronger an individual's non-Western cultural orientation is, the stronger the relation between perceived discrimination and negative outcomes (Deng, Kim, Vaughan, & Li, 2010). Put another way, when immigrant children identify strongly with their family's culture of origin, the detrimental effects of perceived discrimination are strongest.…”
Section: Acculturationmentioning
confidence: 99%
“…Youth who are more acculturated into U.S. culture are found to be at increased risk of externalizing problems (Unger et al., ). Further, although findings have been mixed across studies, one study found that higher Western cultural orientation was associated with less perceived discrimination in a sample of Chinese youth (Deng, Kim, Vaughn, & Li, ). It may be that Latino youth who are more acculturated into U.S. culture both perceive less discrimination and are at higher risk of delinquency engagement, with the experience of CVE exacerbating that risk.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Deng et al. () reported that for Chinese adolescents, high orientation toward Chinese culture amplified the negative impact of discriminatory experiences with respect to delinquent behaviors, whereas high orientation toward Western culture protected Chinese youth against the impact. It is possible that for some youth, ethnic cultural orientation minimizes the impact of discrimination by influencing its salience and/or significance (Umaña‐Taylor & Updegraff, ), as well as coping responses to it (Neblett et al., ).…”
Section: Cultural Orientationmentioning
confidence: 99%